Cytokines and cytokine receptors in fetal growth and development. (May 2001) - Symonds, M. E.; Mostyn, A.; Stephenson, T.
Abstract : The cytokine receptors for growth hormone (GH), prolactin and leptin have a critical role in regulating embryo, placental and/or fetal development, which is dependent on stage of gestation and species. GH and prolactin receptors are detectable from conception, and alterations in the maternal hormonal environment may impact on placental growth from this early stage of gestation. Leptin is critical for conception, but its role in fetal growth remains elusive. During late gestation, when fetal growth accelerates and organ maturation occurs, prolactin and insulin-like growth factor-I may have interactive roles in regulating the growth of specific tissues, including adipose tissue. Prolactin, leptin and GH all have specific effects on fetal and neonatal energy balance, which are mediated in part through promoting lipolysis and/or enhancing the expression of uncoupling proteins. An increased understanding of these interactions is likely to have important implications for a number of potentially pathological conditions, including infection, obesity and hypertension.